Hazard Identification, Risk Assessment, and Risk Control pada PT. X - Kevin Christian (Jurnal Titra, 2023)
PT. X is a company that produces snacks with several kinds of products, namely snacks made from corn, atom beans, and biscuits. This company was founded in 1997 in Surakarta, Central Java. During the time this company was established, several work accidents were recorded that endangered the workers in the field. This final project was carried out using the method of direct observation and interviews with related workers. The purpose of this final project is to identify hazards, assess risks, and propose risk controls. After analyzing, there are 0 potential hazards in the low category, 0 potential hazards in the moderate category, 5 potential hazards in the high category, and 2 potential hazards in the extreme category. The proposal for this company is carried out with 1 risk controls using substitution methods, 6 risk controls using technical engineering methods, 0 risk controls using administrative methods, and 0 risk controls using the method of adding personal protective equipment. If the recommended risk control has been fully implemented by the company, the estimated risk rating that will be given changes to 0 cases in the extreme category, 0 cases in the high category, 3 cases in the high category, and 4 cases in the low category.